Proposta de mensuração de reputação de organizações do terceiro setor segundo o modelo C-OAR-SE - Marcelino, Anderson da Trindade (2013)
Reputation is a construct of diffuse understanding and little consensus. Measuring third sector organizations reputation has been undertaken through the adaptation of instruments designed initially to measure companies reputation. However, not all attributes of reputation are similar for these two types of organizations, especially when the measurement scale is directed to the general public. Thus this paper begins with the following question: how to measure the construct reputation for nonprofit organizations? Such questions will be elucidated through the process of building a scale to measure the construct, thereby configuring the general objective of this dissertation. The method followed in the process of building the OTSs reputation scale is related to the C-OAR-SE model, which was proposed by Rossiter (2002). The scale itself, created in the penultimate step of the model, but idealized in the previous steps, underwent the procedure to test and retest with students of administration at UFPB, and was later tested with a specific organization: Cidade Viva Foundation. The attributes of reputation selected to be in the scale were: reputation, reliability, competence, popular acceptance, internal organization, demand for services, improving the lives of the beneficiaries, environmental concern and importance to society. These attributes must be correlated with the item that measures the level of reputation of the organization that is perceived by users of the scale (the general public), analyzing the correlation coefficients of Spearman. In addition to the items of the scale itself, other items were designed to assess the trustworthiness seeking the perceptions of respondents as well as their feelings and attitudes, but which constitute complements of the scale developed and tested here.